Ectopic adiposity is associated with autonomic risk factors and subclinical cardiovascular disease in young adults. (3rd September 2015) - Lee, Jane J.; Woodard, Genevieve A.; Gianaros, Peter J.; Barinas‐Mitchell, Emma; Tepper, Ping G.; Conroy, Molly B.
<x xml:space="preserve">Abstract</x> Objective To examine the relationship between ectopic adiposity and markers of cardiometabolic risk, autonomic control, and subclinical cardiovascular disease (CVD). Methods Cross‐sectional analyses were performed in 324 subjects with overweight and obesity. Single‐slice CT images were analyzed to calculate thigh muscle attenuation (MA), a measure of ectopic adiposity. Autonomic control was assessed using low‐frequency to respiratory‐frequency heart rate variability (LFa/RFa ratio). Carotid intima‐media thickness (IMT) was a marker of subclinical CVD. Results Among overweight participants, those with low MA had lower HDL‐c, higher LFa/RFa ratio, and subcutaneous thigh fat compared to high MA individuals despite no difference in visceral fat or insulin resistance. Significant associations were not observed in the class I obese group. In the class II obese group, those with high MA had higher triglycerides and insulin levels, yet there was no difference in visceral fat compared to the low MA group. Mean IMT was significantly higher in the low MA compared to the high MA overweight group (0.63 mm vs. 0.58 mm, P = 0.04) but was similar between the low and high MA class II obese groups. Conclusions Excess ectopic adiposity in muscle tissue is associated with metabolic and autonomic risk factors and subclinical CVD, most notably in overweight individuals, independent of insulin resistance and visceral abdominal fat.